2004
DOI: 10.1103/physrevc.69.044904
|View full text |Cite
|
Sign up to set email alerts
|

Universal transition curve in pseudorapidity distribution

Abstract: We show that an unambiguous way of determining the universal limiting fragmentation region is to consider the derivative ͑d 2 n / d 2 ͒ of the pseudorapidity distribution per participant pair. In addition, we find that the transition region between the fragmentation and the central plateau regions exhibits a second kind of universal behavior that is only apparent in d 2 n / d 2 . The ͱ s dependence of the height of the central plateau ͑dn / d͒ =0 and the total charged particle multiplicity n total critically d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…Recently, the phenomenon of limiting fragmentation [54] has received renewed attention [42,53,55,56,57]. The particle density ρ is, in general, a function of both ∆ and the beam rapidity Y .…”
Section: Limiting Fragmentationmentioning
confidence: 99%
“…Recently, the phenomenon of limiting fragmentation [54] has received renewed attention [42,53,55,56,57]. The particle density ρ is, in general, a function of both ∆ and the beam rapidity Y .…”
Section: Limiting Fragmentationmentioning
confidence: 99%
“…Based on the above experimental findings, recently Jeon and collaborators have shown that the total multiplicity obtained at RHIC can be bounded by a cubic logarithmic term in energy [42]. Therefore, we propose here a new parameterization involving a cubic logarithmic term so that the entire p − p experimental data [44,45,46,47,48,49,50,51,52] starting from low energies (i.e.…”
Section: Total Mean Multiplicity Of Charged Hadronsmentioning
confidence: 99%
“…One should use the parameterization upto squared logarithmic term in accordance with Ref. [42]. Hence, using a parameterization for central rapidity density as:…”
Section: Pseudo-rapidity Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the limiting fragmentation curve on energy dependence of particle production has been demonstrated in Ref. [15].…”
Section: Introductionmentioning
confidence: 99%